Vocational education and training in Belgium : short description - (:unkn) unknown (Publications Office of the European Union, 2024)
„This short description places understanding of vocational education and training (VET) in Belgium within its socioeconomic context. It presents key characteristics, system developments, and challenges. Despite the country’s three language-distinct VET systems, and two coexisting in Brussels, with multiple authorities overseeing education, training, and employment, there is political consensus on specific issues. Social partners are actively involved in VET policies at all levels. In all systems, learners can pursue technical or vocational upper secondary VET programmes in school-based or alternating forms, including apprenticeship. Various VET programmes are offered at post-secondary and tertiary levels. The coexistence of three ocial languages poses a significant challenge in all regions, impacting interregional mobility. Current challenges include skill mismatch and skill shortages. While dual learning is popular in the German-speaking Community, there is a negative perception in other regions. Improving the attractiveness of dual VET is high on the policy agenda.“ (editor; BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.2.1 Westeuropa; 370; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Bildungsfinanzierung; Bildungspersonal; Bildungssteuerung; Mehrsprachigkeit; Belgien